HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI DAN POLA ASUH PEMBERIAN MAKAN TERHADAP KEJADIAN STUNTING PADA BALITA DI PUSKESMAS ULAK MUID KABUPATEN MELAWI - Wulandari, Wulandari; Budiastutik, Indah; Alamsyah, Dedi (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Stunting in children under teach five is a risk factor for high rates of mortality. It also reduces the cognitive ability and low motor development, and causes an imbalance body functions. A preliminary study of Health Program Report, Health Department of Kabupaten Melawi, indicated that the stunting prevalence at PuskesmasUlakMuid in April 2016 was 44,1%. It means that there was a significant escalation compared to the stunting cases in 2015 which was only 4%. This study aimed at analyzing the correlation of socioeconomics characteristics, feeding behavior and stunting incidence in children under five at PuskesmasUlakMuid, Kabupaten Melawi. Cross sectional design was used in this study. The data were statistically analyzed by using chi square test.The study revealed that there was relationship of knowledge (p value=0,012 PR=1,826), income (p value=0,021 PR=1,490), egg intake frequency (p value=0,015 PR=1,813), breastfeeding frequency (p value=0,022 PR=1,492), and stunting in children under five cases.Mothers with kids under five need to enhance their health knowledge by actively participating in health socialization, specifically on balanced diet and CIE. Last but not least, they have to breastfeed the baby exclusively for the first 6 months up to 2 years or beyond, and feed the baby more eggs as the animal protein source.Key words : income, knowledge, frequency, consumption, eggs, breastfeeding, Stunting, Puskesmas, UlakMuid, Melawi